2020
DOI: 10.47176/mjiri.34.13
|View full text |Cite
|
Sign up to set email alerts
|

Current practice of percutaneous coronary intervention on patients with acute coronary syndrome in Iran: A prospective observational study

Abstract: The current practice of Iranian physicians for in-hospital "medical management" of patients with acute coronary syndrome (ACS) has already been known. →What this article adds:The present study is the first to describe the current practice of "percutaneous coronary intervention" on patients with ACS in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…In contrast to our study, Bejani et al demonstrated that the incidence of inferior MI was greater in these regions than in other regions [20]. Another study also supported our ndings that the incidence of STEMI was highest in the LAD (56%), followed by the RCA (42%) and LCX (24%) [21]. Although information regarding the distribution of lesions is crucial, why plaques in the LCX are less prone to rupture or why involvement in the proximal segments is more susceptible to rupture remains controversial.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast to our study, Bejani et al demonstrated that the incidence of inferior MI was greater in these regions than in other regions [20]. Another study also supported our ndings that the incidence of STEMI was highest in the LAD (56%), followed by the RCA (42%) and LCX (24%) [21]. Although information regarding the distribution of lesions is crucial, why plaques in the LCX are less prone to rupture or why involvement in the proximal segments is more susceptible to rupture remains controversial.…”
Section: Discussionsupporting
confidence: 83%
“…AMI is classified as STEMI or non-STEMI based on the presence or absence of ST-segment elevation on the electrocardiogram. 24 The ratio of STEMI among patients with AMI was 75.8% 25 and 79.5%.26 The ratio among patients with coronary syndromes was 52.0% 17 and 25.7%. 18 …”
Section: Introductionmentioning
confidence: 97%
“…Chest pain was the most common manifestation of patients with AMI. 10 , 12 17 Small studies covered different periods across the country, from symptom onset to medical contact or arrival at the hospital. Only a minority of patients with AMI (35.7%) arrived at the hospital during the first hour of symptom onset, 7.9% 24 hours after symptom onset in Bandar Abbas, 12 and 69.0% 2 hours after symptom onset in Kashan.…”
Section: Introductionmentioning
confidence: 99%